(untitled) (Fiep Bulletin - online, 2015)
The purpose of this study was to study how school physical education can work the motor and cognitive development of an autistic student enrolled in public Fortaleza and break down prejudices and barriers on the inclusion of the same. The same protocol was submitted to the Motor Development Scale, created by ROSA NETO (2002), adapted for tests covering different areas of motor development. The duration of study was 6 weeks with the student two weekly classes of 55 minutes each. The results indicated that the student has evolved its Motor Age from 92 to 114 months. With this we conclude that the practice of Physical Education should be performed by teachers and encouraged by the general population.